Pengelolaan Pariwisata Pantai Ngiroboyo dan Relasi Antar Aktor Melalui Badan Usaha Milik Desa di Desa Sendang, Kecamatan Donorojo, Kabupaten Pacitan - Sherly Nouvita Riyanto; Yusuf Adam Hilman; Insyira Yusdiawan Azhar; Robby Darwis Nasution; Amartuvshin Sukhee (Jurnal Partisipatoris, 2025)
The management of Ngiroboyo Beach in Sendang Village, Donorojo District, Pacitan Regency, has gone through various stages of development since 2016. Initially managed by the Village Youth Organization, management was transferred to the Subur Makmur Village-Owned Enterprise (BUMDes) in 2019. This BUMDes developed Ngiroboyo Beach with the aim of improving the village economy through tourism. This study uses a qualitative descriptive approach to explore the application of Good Governance principles in the management of Ngiroboyo Beach and identify the relationships between actors involved in the management of this tourist area. The principles of Good Governance are realized through transparency, accountability, community participation, and cooperation between sectors. This study shows that close collaboration between the village government, BUMDes, and the local community is the key to successful management. They work together in decision making, tourism operations, and environmental conservation. Innovation and adaptation, such as the use of technology, also play an important role. The success of Ngiroboyo Beach proves that the principles of Good Governance can make village tourism a driving force for a sustainable economy.